ANALISIS “BERTEMAN DENGAN KERAGAMAN” PADA BUKU KELAS II BERDASARKAN KELAYAKAN BUKU BSNP - Nisrina Tri Riana; Panca Dewi Purwati; Romzi Habibie; Clarita Ferdina Isna pertiwi; Tias Lely Maulita; Feisya Citra Dhiya Riznandya (Jurnal Bastra (Bahasa dan Sastra), 2025)
This study aims to analyze the language and spelling feasibility of Chapter V in the 2021 Indonesian language textbook for second-grade elementary school students, themed “Making Friends in Diversity.” Using a qualitative descriptive method with content analysis and linguistic error analysis, the study evaluates the textbook's content alignment with learning objectives, character education, and linguistic accuracy. Data were collected through document review, observation sheets, student journals, and guided discussion outcomes. The findings indicate that the chapter content appropriately integrates character values such as empathy, tolerance, and self-confidence through contextual fables and active learning activities. However, several issues were identified in linguistic structure, including the use of non-standard words like “minder,” incomplete or ambiguous sentence constructions, and punctuation errors in direct speech. Visually, the book employs child-friendly design and illustrations, although some graphics lack relevance to the narrative. The transition between narrative and exercises is often abrupt, reducing instructional coherence. Despite meeting most feasibility indicators, improvements are needed in language structure and narrative cohesion to enhance the effectiveness of the book as a learning medium. The study recommends revising ambiguous sentences, ensuring accurate spelling and punctuation, and aligning illustrations with textual content. Strengthening both linguistic and visual elements can significantly contribute to fostering proper language habits and instilling positive character traits in early-grade learners.